DEIKSIS PADA PEMBERITAAN PRESIDEN INDONESIA DI TEMPO.CO DAN KOMPAS.COM - Yundanti, Nandifa Hastha; Ekawati, Mursia; Herpindo, Herpindo (DIALEKTIKA JURNAL PENDIDIKAN BAHASA INDONESIA, 2024)
The research entitled "Deixis on the 2022 Indonesian Presidential News in Tempo.co and Kompas.com is motivated by one of the meanings of language used in communication, namely the use of deiksis which involves context and obtaining appropriate understanding. This research only focuses on the form of deiksis on the 2022 Indonesian presidential news in Tempo.co and Kompas.com. This study used a qualitative research approach. The subjects in this study are deiksis on the news of the Indonesian president in 2022 in Tempo.co and Kompas.com. The method used by the researcher is the listen method with a recording technique. The method of data analysis, namely the referential method with the determining element sorting technique (PUP) and the equalizing banding technique (HBS). The results of this study found 39 deiksis data. The data consists of 20 deiksis data in Tempo.co and 19 deiksis data in Kompas.com. Based on the results of this study, it can be concluded that the form of deiksis is more commonly found in Tempo.co and differences in the use of deiksis forms can be found in Tempo.co and Kompas.com. Keywords: pragmatics, deixis, presidential news